2015
DOI: 10.13053/rcs-94-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparativa de algoritmos bioinspirados aplicados al problema de calendarización de horarios

Abstract: Resumen. El problema de calendarización de eventos está presente en diversas organizaciones como lo son escuelas, hospitales, centros de transporte, etc. La calendarización de actividades en una universidad tiene como propósito el garantizar que todos los estudiantes tomen sus asignaturas requeridas apegándose a los recursos que están disponibles. El conjunto de restricciones que debe contemplarse en el diseño de horarios involucra a los alumnos, maestros e infraestructura. En este trabajo se muestra que media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
12

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 22 publications
0
4
0
12
Order By: Relevance
“…Those techniques are genetic, memetic, and immune system algorithms. After comparing all the algorithms, the authors concluded that the GA offers several advantages [20]. Xiang et al used, in 2015, ant colony optimization (ACO) to solve a surgery scheduling problem.…”
Section: A Brief Review Of the Specialized Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Those techniques are genetic, memetic, and immune system algorithms. After comparing all the algorithms, the authors concluded that the GA offers several advantages [20]. Xiang et al used, in 2015, ant colony optimization (ACO) to solve a surgery scheduling problem.…”
Section: A Brief Review Of the Specialized Literaturementioning
confidence: 99%
“…We will view the application of the crossover operator with an example of a scheduling problem with a set of nine surgeries with the next durations (200,160,200,490,200,20,300,140,300), and ORs with a capacity of 510 min. Figure 4 shows the two chromosomes that we will be using for the example.…”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The assignment of schedules problem, is a recurrent situation in all educational institutions [1], where in each scholar period the schedule of the students is planned; assigning signatures, classrooms and teachers, with the objective of avoiding an overlap of hours [2]. Therefore it can be defined as a decision-making problem for the assignment of educational resources (students, teachers, classrooms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…De particular, el diseño de horarios en las instituciones educativas no ha podido realizarse de manera generalizada, debido a la gran cantidad de variantes que tiene, entre las más importantes se encuentran: alumnos, docentes, plan de estudios, sistema de educación e inmuebles con los que dispone cada institución [2].…”
unclassified